2016
DOI: 10.1111/jopr.12544
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Bite Force of Edentulous Patients before and after Dental Implant Rehabilitation: Long‐Term Follow‐Up and Facial Type Influence

Abstract: There was no statistically significant relation between MBF and the dominant chewing side. It can be concluded that mandibular rehabilitation with dental implants improves MBF independent of the facial pattern and dominant chewing side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
4
7
0
4
Order By: Relevance
“…In our study, the BF of IMO users was similar on both sides, indicating that IMO use equalizes the BF on both sides. This finding is in agreement with the results of Melo et al (26), but contrasts with the results of Rismanchian et al (11), who found that the BF in the dominant side was 21.7% higher. Nonetheless, the superior retention and stability provided by IMO likely allow for a more balanced mastication in most cases.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the BF of IMO users was similar on both sides, indicating that IMO use equalizes the BF on both sides. This finding is in agreement with the results of Melo et al (26), but contrasts with the results of Rismanchian et al (11), who found that the BF in the dominant side was 21.7% higher. Nonetheless, the superior retention and stability provided by IMO likely allow for a more balanced mastication in most cases.…”
Section: Discussionsupporting
confidence: 90%
“…For this reason, studies have been conducted in which mastication on the habitual chewing side is used in the evaluation of MP [6,9,12,14,15,21,[28][29][30]. However, some reports have concluded that there are no functional differences between the chewing sides [31]. It is necessary to be careful when selecting the habitual chewing side.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to be careful when selecting the habitual chewing side. It has been pointed out that there are doubts regarding the validity of simply asking the participant which side is easier to chew on [31,32]. An electromyographic method [32] or a method of examining the first chewing side after the start of mastication [33] is used as more objective method selection the habitual chewing side.…”
Section: Discussionmentioning
confidence: 99%
“…G * Power software version 3.1 (Kiel University) was used to calculate the sample size. The effect size was set to 0.8, with reference to previous studies [11,14] (d = 0.65, 0.88) [20]. When the α value was set to 0.05, detection power was set to 0.8, and effect size d to 0.8, the required number of samples was 52.…”
Section: Sample Sizementioning
confidence: 99%
“…Muscle echo intensity can be evaluated by an ultrasonic diagnostic device that identi es non-contractile tissues, such as fat and brous tissue in the muscle, and indicates muscle quality [10]. Several previous studies have reported that MA, MOF, and MMT are greatly improved with dental prosthetic treatments such as implants and dentures [11][12][13]. In addition to prosthetic treatment, isometric exercise is used as a method of maintaining oral function.…”
Section: Introduction Background and Objectivementioning
confidence: 99%